Comparison Analysis of Total Cholesterol Level Examination Between Photometry and 3 Parameters Point of Care Testing Device - Perdina Nursidika; Wikan Mahargyani; Fitri Kurnia Anggraeni (Medical Laboratory Technology Journal, 2018)
Total cholesterol is the composition of many substances including cholesterol, triglycerides, LDL cholesterol, and HDL cholesterol. Cholesterol examination is one of the most frequent tests required in the laboratory to monitor vascular and cardiovascular diseases. Most clinical pathology laboratories use photometer to perform clinical chemistry checks. Cholesterol testing can also be done with Point of Care Testing (POCT) which has a working principle of biosensor technology. This research method is experimental, using 40 samples that can represent normal and pathological levels. All samples will be checked for total cholesterol with a photometer of CHOD-PAP method and 3 POCT Lipid Pro. The results showed linear regression y = 0.955x + 1.8325 with R2 of 0.9955. The linear regression value is calculated by Total Error (TE), while the Total Error Allowable (TEa) cholesterol is 10%. The bias value is 0.31%, TE for normal level = 5.92% and TE for high pathological level = 3.00%, it can be stated the result of examination can be compared or accepted. The% TE value obtained is less than the TEa value of cholesterol. It can be concluded that the total cholesterol results examined by the photometer and LipidPro are comparable. For further research it is advisable to use a total cholesterol sample that has a value of more than 400 mg/dL.